Mengukur Kinerja Dosen dan Admin di UKDC dengan Productivity Metrics - Hartanto, Andre; Putri, Padmavati Darma (LP2M Institut Teknologi dan Bisnis ASIA Malang, 2024)
This research aims to evaluate the performance of faculty members and administrators in the Computer Science Study Program at Darma Cendika Catholic University using productivity metrics. Data for this study were collected through surveys, interviews, observations, and document analysis. The study identified various performance metrics, including participation in research, teaching quality, administrative efficiency, and adaptation to technology. The collected data are valid and measured across multiple aspects, such as the number of scholarly publications, response rates to document collection, and the accuracy of class schedules. The results of this research are expected to provide insights into the contributions of faculty members and administrators to the effectiveness of the Computer Science Study Program. The implications of the research results involve recommendations for performance improvement, staff empowerment, and administrative process enhancement. This study is anticipated to serve as a guide for other higher education institutions in implementing similar productivity metrics to enhance operational quality and efficiency.